Model Matematika Optimasi Biaya Dan Waktu Pada Penjadwalan Proyek Konstruksi Teknik Sipil - Zega, Berkat (Jurnal Ilmu Teknik Sipil Indonesia, 2026)
Civil engineering construction projects are highly complex and therefore require effective planning and control, particularly in terms of cost and time. Project delays and cost overruns frequently occur due to suboptimal scheduling practices. This study aims to develop a mathematical model for cost and time optimization in construction project scheduling. A quantitative approach using mathematical modeling is employed, in which the scheduling problem is formulated as an objective function to minimize total project cost subject to duration constraints and precedence relationships among activities. An initial analysis is conducted using the Critical Path Method (CPM) to identify critical activities as the basis for optimization. The optimization model is solved using linear programming techniques with the assistance of optimization software. The results indicate that the proposed mathematical model is capable of producing a more efficient project schedule compared to conventional scheduling, as evidenced by a reduction in project duration and total cost. Furthermore, the time–cost trade-off analysis reveals the existence of an optimal project duration that results in minimum total cost. This study is expected to contribute theoretically to the development of construction management knowledge and practically as a decision-support tool for planning and controlling civil engineering construction projects.